2017
DOI: 10.1371/journal.pone.0172310
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of global drivers of vaccine hesitancy in 2014—Looking beyond safety concerns

Abstract: Vaccine hesitancy has become the focus of growing attention and concern globally despite overwhelming evidence of the value of vaccines in preventing disease and saving the lives of millions of individuals every year.Measuring vaccine hesitancy and its determinants worldwide is important in order to understand the scope of the problem and for the development of evidence-based targeted strategies to reduce hesitancy.Two indicators to assess vaccine hesitancy were developed to capture its nature and scope at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
125
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(137 citation statements)
references
References 10 publications
10
125
0
2
Order By: Relevance
“…This study was approved by the Research Ethics Committee of the São Leopoldo Mandic University, registration n. 51606415. 8 Table 2 Distribution of the respondents (n = 952) by age group, marital status, income and level of education.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was approved by the Research Ethics Committee of the São Leopoldo Mandic University, registration n. 51606415. 8 Table 2 Distribution of the respondents (n = 952) by age group, marital status, income and level of education.…”
Section: Methodsmentioning
confidence: 99%
“…While some anti-vaccine sentiments date back to the 1800s -with some common themes, such as safety concerns, religious resistance against interfering with "God's plan" or mother nature, and libertarian resistance against mandates -the nature and scope of more recent episodes of vaccine hesitancy and refusal have new modes of spread and pertain to a greater number of vaccines and combinations of vaccines 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, multiple factors such as religious beliefs, geographic barriers, parent-provider relationship, perceived risk of adverse events following immunization (AEFI), lack of knowledge about vaccination, and disease risk perception give rise to vaccine hesitancy. [7] A survey conducted by WHO and UNICEF showed that vaccine hesitancy emerged a decade ago; [8] however, it has gained attention due to the current changing scientific, cultural, medico-legal, and media environments, despite all the efforts made to increase the awareness and increase the vaccines uptake. [9] The trend has been realized in several countries across the world including United Kingdom, United States, and India.…”
Section: Introductionmentioning
confidence: 99%
“…1,10 To counteract this ominous trend, it is critical to monitor individuals who have concerns about vaccination and to develop appropriate strategies so that vaccine hesitancy would not transform into absolute refusal in the form of antivaccination movement. 11 The aim of this study was to determine the attitudes of parents regarding vaccine hesitancy and refusal (V-HR) and to derive information that would help define and develop appropriate strategies to tackle this rising problem.…”
Section: Introductionmentioning
confidence: 99%